Climate warming effects in the tropical Andes: first evidence for upslope shifts of Carabidae (Coleoptera) in Ecuador. Issue 4 (29th April 2016) - Moret, Pierre; Aráuz, María de los Ángeles; Gobbi, Mauro; Barragán, Álvaro
Abstract: In order to assess the impact of global warming on the biodiversity of the tropical high Andean páramo ecosystem, we compared historical and recent surveys of ground beetle communities along elevational gradients of the Pichincha volcano (Northern Ecuador). The studied datasets date to 1880, 1985/86 and 2013/15. From 1880 to 1985, the bottom range of at least one stenotopic and wingless high‐altitude species, Dyscolus diopsis, has shifted approximately 300 m upward, with the resulting area reduction of more than 90% from >12 km 2 to <1 km 2, which highlights the probability of future local extinctions on the Pichincha as well as on other mountains of Ecuador. Over a shorter period of time, the comparison of the 1985/86 and 2013/14 datasets indicates that the lower limit of the superpáramo ground beetle community has shifted upwards from circa 4300 m to circa 4400 m. Different individual responses are recorded among the species. Some of them did not experience any significant change, whereas the upper limit of one of the grassland generalists has shifted upwards at least 400 m in 28 years. These results suggest that the response to global warming varies from one species to the other, depending on their degree of specialisation and tolerance. They call for the implementation of a monitoring programme that would use carabid assemblages as an indicator of the impact of climate change on the páramo ecosystem, in combination with other proxies.